Role of the Gut-Liver Axis in Driving Parenteral Nutrition-Associated Injury - Christine Denton; Amber Price; Julie Friend; Chandrashekhara Manithody; Keith Blomenkamp; Matthew Westrich; Vindhya Kakarla; William Phillips; Joseph Krebs; Armando Salim Munoz Abraham; Hector Osei; Ajay Kumar Jain (MDPI AG, 2018)
For decades, parenteral nutrition (PN) has been a successful method for intravenous delivery of nutrition and remains an essential therapy for individuals with intolerance of enteral feedings or impaired gut function. Although the benefits of PN are evident, its use does not come without a significant risk of complications. For instance, parenteral nutrition-associated liver disease (PNALD)-a well-described cholestatic liver injury-and atrophic changes in the gut have both been described in patients receiving PN. Although several mechanisms for these changes have been postulated, data have revealed that the introduction of enteral nutrition may mitigate this injury. This observation has led to the hypothesis that gut-derived signals, originating in response to the presence of luminal contents, may contribute to a decrease in damage to the liver and gut. This review seeks to present the current knowledge regarding the modulation of what is known as the "gut-liver axis" and the gut-derived signals which play a role in PN-associated injury.